The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijms19092506
|View full text |Cite
|
Sign up to set email alerts
|

The Sugar-Signaling Hub: Overview of Regulators and Interaction with the Hormonal and Metabolic Network

Abstract: Plant growth and development has to be continuously adjusted to the available resources. Their optimization requires the integration of signals conveying the plant metabolic status, its hormonal balance, and its developmental stage. Many investigations have recently been conducted to provide insights into sugar signaling and its interplay with hormones and nitrogen in the fine-tuning of plant growth, development, and survival. The present review emphasizes the diversity of sugar signaling integrators, the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 469 publications
(493 reference statements)
3
117
0
1
Order By: Relevance
“…6) and the small growth phenotypes of the pp7l mutant ( Fig. 1) would be in accordance with sugar-signaling regulators playing a central role in the regulation of starch metabolism (Sakr et al, 2018;Wurzinger et al, 2018). With its predicted function as an inactive Ser/Thr phosphatase, it is unlikely that it is a transcription factor and future studies will have to clarify the molecular function of PP7L.…”
Section: Pp7l Contributes To the Tolerance To Abiotic Stressessupporting
confidence: 56%
“…6) and the small growth phenotypes of the pp7l mutant ( Fig. 1) would be in accordance with sugar-signaling regulators playing a central role in the regulation of starch metabolism (Sakr et al, 2018;Wurzinger et al, 2018). With its predicted function as an inactive Ser/Thr phosphatase, it is unlikely that it is a transcription factor and future studies will have to clarify the molecular function of PP7L.…”
Section: Pp7l Contributes To the Tolerance To Abiotic Stressessupporting
confidence: 56%
“…As mentioned above, high sugar levels may explain a reduction of apical dominance in response to environmental or genetic factors increasing the source/sink balance within the plant. Sugars act through different signaling pathways, including those related to sucrose-, hexokinase-, glycolysis (Li & Sheen, 2016; Sakr et al , 2018; Wingler, 2018). It has been suggested that sucrose could promote bud outgrowth in a signaling manner in rose and pea (Barbier et al , 2015b; Fichtner et al , 2017) and further experiments are required to determine the molecular mechanisms underlying the interactions between sugar availability and auxin.…”
Section: Discussionmentioning
confidence: 99%
“…Suc, hexoses, and trehalose also function as signal molecules that participate in control of nutrient homeostasis, stress response, and organ development (Paul et al, 2008;Lastdrager et al, 2014). In addition, hexokinase 1 (HXK1) and Suc non-fermenting-1-related protein kinase (SnRK1) were reported to be related to sugar signaling, as two dependent pathways (Moore et al, 2003;Broeckx et al, 2016;Sakr et al, 2018). Although the relationship between trehalose-6-phosphate and Suc signaling in plant remains to be fully resolved, it is known that trehalose-phosphate synthase (TPS) plays an important role in controlling the ratio of trehalose-6-phosphate and Suc (Figueroa and Lunn, 2016;Sakr et al, 2018).…”
mentioning
confidence: 99%